The effects of molecular fine structure on rice starch granule gelatinization dynamics as investigated by in situ small-angle X-ray scattering. (December 2021) - Xu, Jinchuan; Li, Zhihang; Zhong, Yuyue; Zhou, Qi; Lv, Qi; Chen, Ling; Blennow, Andreas; Liu, Xingxun
Abstract: Dynamic changes of rice starch granules selected for different amylose contents were analyzed in excess water while heated in-situ in a small-angle X-ray scattering (SAXS) instrument. Normal rice starch (NS) and rice starch with high amylopectin (HAP) and high amylose (HAM) were used as models. A 1D linear correlation function and a combination power-law and Gaussian function were used to extract the starch lamellar structure parameters and the fractal dimension, ordering and distribution of starch lamellae from SAXS data. For the resulting starch paste/gels, a model of two-correlation length was fitted to afford the correlation length (ξ) for the paste/gel system. The results showed that HAM exhibited higher long period (LP) and thickness of the crystalline layers ( d c ) values than HAP and NS. However, HAP showed the highest ordering lamellar structure. HAP granules were more thermostable than the amylose containing starches. For the gelatinized starches, HAM showed the highest correlation length values but these notably decreased with increasing temperature indicating strong chain segment interaction. This research reveals essential structural changes in lamellae of rice starch granules and rice starch gel structure, which provides potentially useful in the working of starch-based foods and materials. Graphical abstract: Image 1 Highlights: Amylose content affect the gelatinization dynamics of the lamella. HAP granules were more thermostable than amylose-containing granules. HAM granules had high long period distance and d c and were less thermostable. HAM displayed larger correlation lengths, which decreased with temperature.